(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article explores the classification of liabilities in joint-stock companies, as well as the procedures for accounting and reporting them based on their duration and types. In accordance with International Financial Reporting Standard (IFRS) No. 12, the article examines existing issues related to the recognition of deferred tax liabilities in accounting and offers proposals aimed at resolving these challenges. Additionally, relevant suggestions are made for presenting current liabilities in a separate line in financial statements when they significantly affect indicators that reflect the financial condition of the company and are important for investor decision-making.